Performance Measurement Under Asymmetric Information and Investment Constraints - Gendron, Michel; Genest, Christian (Journal of Finance, 1990)
The fact that investment policies are often restricted appears to have been neglected in the performance measurement literature. This paper, using a standard information model, shows how the introduction of constraints on the proportion of assets to be invested in the market affects the expected portfolio returns and the value of a portfolio manager's performance. The results are related to the classical Treynor and Mazuy (1966) conjectures about characteristic lines.